Analisis Hasil Belajar Astronomi Berdasarkan Kuis Wordwall di Kelas dan di Rumah - Baihaqi, Habibah Khusna; Nuraini, Lailatul Nuraini; Zakwandi, Rizki (Journal of Teaching and Learning Physics, 2025)
This study analyzes the differences in astronomy learning outcomes based on the timing of WordWall post-tests administered either in-class or at home. Conducted in two face-to-face classes with 70 university students, one class completed the quiz immediately after instruction, while the other completed it later from home. A quantitative approach was applied using descriptive statistics and the Mann-Whitney U test to examine differences in mean scores and variability. The results showed that students who took the quiz at home had slightly higher average scores but greater score dispersion. In contrast, students who completed the quiz in class had more consistent results. These findings suggest that immediate post-tests better reflect uniform understanding than delayed assessment. Factors influencing these differences include student motivation, regulation, and engagement. The study highlights the importance of post-test timing when using digital tools like WordWall for evaluating learning outcomes in astronomy education.